(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The integration of artificial intelligence (AI) in educational contexts has the potential to revolutionize language instruction, particularly for young learners. This study investigates the role of ChatGPT, an advanced language model, in teaching English to children aged 6-10. By analyzing its impact on student engagement, personalized learning experiences, and language acquisition, this research aims to evaluate the effectiveness of ChatGPT as a supplementary tool in language education. Data were collected through experimental teaching sessions, pre- and post-assessments, teacher observations, and student interviews. The results demonstrate that ChatGPT enhances vocabulary retention, grammar understanding, and overall motivation among young learners, suggesting its valuable contribution to modern educational practices.